Degree of conversion of resin composite cured by light through a translucent fiber posts. - Somchai Urapepon (2015)
PURPOSE: This study evaluated the depth of cure of resin composite cured by light through a translucent fiber post. MATERIALS AND METHODS: The opaque plastic tubes in various lengths of 2, 4, 6, 8, 10, 12, 14 mm. were filled with resin composite in which two different translucent fiber posts were inserted into the center and photo-polymerized for 40 seconds. The degree of conversion of the cured composite at bottom surface were examined using Fourier transform infrared attenuated total reflection spectrometer (FTIR/ATR) at 0.1, 0.5 and 1.0 mm apart from the post surface. RESULTS: The degree of conversion of the 0.1 mm, 0.5 mm, 1.0 mm apart from the post surface was highest at the 2 mm level and continuously decreased when the distance from the light source was increased and drastically decreased when the depth from the top of the post was greater than 4-6 mm. For each level, the highest degree of conversion was at 0.1 mm from the post surface and decreased continuously when the distance apart from the post surface was increased. CONCLUSION: The quantity of light transmission depends on the type of post and the light transmission capability of the post, especially after 4-6 mm depth and the area further apart from the post surface, are insufficient for clinical light activation of resin composite.